2011
DOI: 10.1007/s10596-011-9224-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to robust design and probabilistic risk assessment for CO2 storage in geological formations

Abstract: CO 2 storage in geological formations is currently being discussed intensively as a technology with a high potential for mitigating CO 2 emissions. However, any large-scale application requires a thorough analysis of the potential risks. Current numerical simulation models are too expensive for probabilistic risk analysis or stochastic approaches based on a brute-force approach of repeated simulation. Even single deterministic simulations may require parallel high-performance computing. The multiphase flow pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…In the work by Oladyshkin et al, 16 design variables are integrated into the PCE approximations, i.e., each design variable or parameter is assigned with a hypothetical distribution and treated as the uncertainty input (parameters). Consequently, the model output becomes some polynomial function of the model input and the design variables.…”
Section: Uncertainty Analysis and Injection Optimization With Pcesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the work by Oladyshkin et al, 16 design variables are integrated into the PCE approximations, i.e., each design variable or parameter is assigned with a hypothetical distribution and treated as the uncertainty input (parameters). Consequently, the model output becomes some polynomial function of the model input and the design variables.…”
Section: Uncertainty Analysis and Injection Optimization With Pcesmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] These methods mainly fall into two categories: intrusive approaches and nonintrusive ones. Intrusive methods involve substituting the PCE approximations into the governing equations and using a Galerkin technique 17 and a discretization scheme to solve for the coefficients in the expansion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oladyshkin and Nowak observed that as every set of random data, as well as a continuous or discrete PDF, can be described using the moments without making any assumptions about the shape or existence of a suitable probability distribution, the moments provided a very general approach to propagate data without requiring the determination of deterministic PDFs. Oladyshkin and Nowak [7] promoted this concept in the geo-sciences by successfully applying it to identify uncertainties in carbon dioxide storage in geological formations [15,16,17] and also for robust design [18]. Moreover, Oladyshkin and Nowak presented a derivation of the optimal orthogonal polynomials from the moments.…”
Section: Introductionmentioning
confidence: 99%